2015
DOI: 10.1103/physrevd.92.054504
|View full text |Cite
|
Sign up to set email alerts
|

Free-form smearing for bottomonium andBmeson spectroscopy

Abstract: To obtain high-quality results from lattice QCD, it is important to use operators that produce good signals for the quantities of interest. Free-form smearing is a powerful tool that helps to accomplish that goal. The present work introduces a new implementation of free-form smearing that maintains its usefulness and reduces its computational time dramatically. Applications to the mass spectrum of B, B s , B c and bottomonium mesons show the effectiveness of the method.Results are compared with other lattice Q… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
33
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 37 publications
5
33
1
Order By: Relevance
“…So far, different types of quark potential model have been applied in studying the bottomonium spectrum, including the nonrelativistic [5,[27][28][29][30], the semirelativistic [31,32], the relativized [33][34][35], and the relativistic [36,37] versions. The bottomonium spectrum has also been studied by the Bethe-Salpeter equation [38], the coupled channel model [39][40][41][42], the QCD sum rule [43,44], the Regge phenomenology [45][46][47][48], the lattice QCD [49][50][51], and other method [52]. 2 Belle also measured R ≡ σ(h b (np)π + π − ) σ(Υ(2S )π + π − ) (n = 1, 2) and the result indicated that the Υ(5S ) → h b (np)π + π − and Υ(5S ) → Υ(2S )π + π − processes have the similar production ratios [19].…”
Section: Introductionmentioning
confidence: 99%
“…So far, different types of quark potential model have been applied in studying the bottomonium spectrum, including the nonrelativistic [5,[27][28][29][30], the semirelativistic [31,32], the relativized [33][34][35], and the relativistic [36,37] versions. The bottomonium spectrum has also been studied by the Bethe-Salpeter equation [38], the coupled channel model [39][40][41][42], the QCD sum rule [43,44], the Regge phenomenology [45][46][47][48], the lattice QCD [49][50][51], and other method [52]. 2 Belle also measured R ≡ σ(h b (np)π + π − ) σ(Υ(2S )π + π − ) (n = 1, 2) and the result indicated that the Υ(5S ) → h b (np)π + π − and Υ(5S ) → Υ(2S )π + π − processes have the similar production ratios [19].…”
Section: Introductionmentioning
confidence: 99%
“…The heavy quark fields in this theory are represented by Pauli spinors coupled to gauge fields, and quark-anti-quark pair creation of the heavy quark is not allowed. Lattice NRQCD has been used to study bottomonia properties at zero temperature [18][19][20][21][22][23][24][25]. Attempts to calculate bottomonia spectral functions at non-zero temperatures using lattice NRQCD have also been reported [26][27][28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…Extended operators are widely used to study quarkonia properties at zero temperature [18][19][20][21][22][23][24][25]. Correlators of extended operators have a better projection onto quarkonium states and are less sensitive to the continuum, i.e., the bound-state contribution to these correlators is sig-nificantly larger.…”
Section: Introductionmentioning
confidence: 99%
“…Naturally first principle calculations using lattice QCD are quite essential to study these hadrons. However, unlike quarkonia, lattice study of bc hadrons are confined only to a few calculations [58,[63][64][65][66]. In this work we carry out a detailed lattice calculation of the ground state energy spectra of all low lying bc hadrons (showed in Table I) with very good control over systematics and predict their masses most precisely to this date.…”
mentioning
confidence: 99%